HUBUNGAN KEPATUHAN MINUM ANTIRETROVIRAL DENGAN KUALITAS HIDUP PASIEN HIV/AIDS DI POLIKLINIK MAWAR RSUD KOLONEL ABUNDJANI BANGKO - Esti, Amira; Yolanda, Mona; Epida, Marta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
HIV is a type of virus that attacks the body's immune system. Infection HIV causes damage to the patient's general system. System glitches continued immune response can result in worsening progression of HIV infection become AIDS. This can be controlled with antiretrovirals (ARV). ARV function suppresses the replication of HIV viruses in the body, thereby improving the quality of life of HIV/ AIDS patients. This research aims to determine compliance, quality of life and the relationship between compliance and quality of life of HIV/ AIDS patients. The university research used an observational analytical design with a cross- sectional approach. The population in this study consisted of all HIV/ AIDS patients who received ARV therapy at Polklunk Mawar, Colonel Abundjani Bangko Regional Hospital with a sample of 39 people using a total sampling technique. Data analysis used non- parametric statistics with the chi- square test. The results of the research showed that 35 respondents (89.7%) were adherent to taking ARVs, 34 respondents (87.29) had good quality of life. valne=0.004 p0.05) at Poliklinik Mawar RSUD Colonel Abundjani Bangko Keywords : HIV/AIDS, adherence, quality of life, ARVs